Techniques for Fixing Anterior Cruciate Ligament Tibial Avulsion Fractures in Multiligament Knee Injuries - Francis Jia Yi Fong MBBS; Glenys Mu En Poon MBBS, MRCS (Ed); Yee Han Dave Lee MBBS, FRCS (Tr&Ortho) (SAGE Publishing, 2023)
Background: In patients with multiligament knee injuries, anterior cruciate ligament (ACL) tears are often reconstructed. Recent studies have shown good results when the ACL tibial avulsions are repaired. The advantages of ACL tibial avulsion repair are the preservation of the native anatomy, reduction in donor site morbidity, and lower risk of tunnel convergence. Indications & Technique Description: We show 2 techniques for repairing ACL tibial avulsion fractures. The first case describes the use of hybrid fixation (screw and suture), with staged repair and reconstruction in a patient with high-energy knee fracture-dislocation. The second case describes the use of suture ACL repair via tunnels in a patient with a low-energy knee dislocation and an ACL tibial avulsion fracture. When repairing ACL tibial avulsion fractures, screw fixation is recommended for larger tibial fragments. In smaller comminuted fragments, tying sutures passed through the ACL via tibial tunnels may be more appropriate. Results: Several studies have demonstrated good postoperative results in patients following the fixation of ACL tibial avulsion fractures. Both screw and suture fixation are effective methods of repairing ACL tibial avulsion fractures and have similar postoperative outcomes. It has been found that screw fixation is associated with a higher risk of subsequent surgery and implant removal than suture fixation. Conclusion: The repair of ACL tibial avulsion fractures in multiligament knee injuries is an alternative to ACL reconstruction that demonstrates excellent postoperative patient outcomes, good patient satisfaction, and good return to sports. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form.